Bahasa Inggris - Sri Bella Timbuli; Agusrianto Yusuf; Yusri R Halada (LPPM Universitas Bina Mandiri Gorontalo, 2020)
The fungus Candida albicans can cause a condition called candidiasis, which is a disease of the mucous membranes, mouth, vagina and digestive tract. The purpose of this study was to identify the fungus Candida albicans in elderly women with incontinence at the Griajanti Nursing Home, Gorontalo City.This research method uses the approach used in this study is a qualitative approach. Qualitative research is a descriptive study that tends to use analysis, namely to describe the presence of Candida albicans in the urine of elderly women with incontinence in the Griajanati Nursing Home, Gorontalo City and the type of research used in this study is descriptive. Descriptive research aims to describe and describe a symptom, event and occurrence that occurs.The results showed that some of the Candida albicans fungus was found in the urine of elderly women with incontinence who were successfully isolated in pure form. With the characteristics of colonies on solid medium slightly rising from the surface of the medium with a smooth, slippery or folded surface, yellowish white in color and smelling of yeast.